Em busca da autonomia da mulher: análise do contrato de comunicação da Marcha das Vadias - Ferreira, Juliana Cristina da Silva (2017)
This research examines how the Slut Walks enunciator constituted her communication contract from nodal point “female body anatomy”, thereby also analyses the discursive displacement undertaken by the enunciator when antagonizing the hegemonic discourse of male domination. The research corpus is composed by Facebook page analysis “Marcha das Vadias Sampa” from the period of May 2012 to July 2016, beyond direct observation of “V edição da Marcha das Vadias” and more activities performed by Coletiva Marcha das Vadias Sampa in 2015. This research is inserted in two research universes: feminism and discourse. Hence, in the first chapter we dedicated in understand how the Slut Walks built itself as XXI century feminist movement with contribution of theoreticians Michelle Perrot and Carla Garcia. In the next chapter, we present the Slut Walks as discursive identity in a social field of linguistic disputes with theoretical reference of Ernesto Laclau and Chantal Mouffe. In sequence, we analyse the walk calling from contributions of José Luiz Aidar Prado. Finally, in the last chapter we dedicate in the comprehension of Slut Walks demobilization in São Paulo city, and the way that the proposed discourse from the movement is denied and accepted by other feminist discursive entities